(untitled) (Fiep Bulletin - online, 2014)
The objective of the present I study was evaluate the association between the use of exercises multiarticulares in the series of adaptation of the students beginners and exercises multiarticulares in students that practice sport, in the vision of the professional of Physical Education. The methodology was of descriptive stamp with typology EQUAL-Q simple, with 51 professionals of different towns, filling questionnaire with division of EQUAL-Q 1 and 2. The result for analysis are in graphics where presents the answers of the professionals of Physical Education, that show a vision more personalized about exercises multiarticulares than in agreement with literatures. Concluded the utilization of the exercises multiarticulares of innapropriate way and that there is need of awareness for the use of the mesmos.